Public Accountants’ Ethical Perceptions in Dealing with Client Pressure: A Qualitative Study of Accounting Firms - Shanum, Arsyila Luthfia; Purwati, Astri Ayu; Deli, Mazzlida Mat (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study explores the ethical perceptions of public accountants in Jakarta when facing client pressures, employing a qualitative phenomenological approach. Through in-depth interviews with licensed auditors from mid-sized and large accounting firms, the research identifies common ethical dilemmas, decision-making processes, and the influence of organizational and cultural factors. Findings reveal that auditors frequently encounter pressures to overlook discrepancies or adjust financial statements, leading to conflicts between professional ethics and client satisfaction. The study highlights the role of firm culture, time budget pressures, and individual values in shaping ethical behavior. Strategies such as adherence to ethical guidelines, client communication, and seeking guidance from superiors were noted as key to maintaining integrity. The research underscores the need for robust ethical frameworks and continuous training to support auditors in navigating ethical challenges effectively.